PREPARASI BIODIESEL DARI MINYAK JELANTAH KELAPA SAWIT - I W. Suirta (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Synthesis of biodiesel from used cooking oil was carried out in two step reactions i.e esterification andtransesterification. The biodiesel obtained was analysed using gas chromatography and mass spectrometer (GC-MS).The quality was determined by comparing its physico chemical properties and compared to the Jerman Standard DINV 51606.The result of GC-MS showed 6 peaks coresponding to six methyl ester(biodiesel): methyl myristate, methylpalmitate, methyl linoleate, methyl oleate, methyl stearat and methyl arachydate. The biodiesel obtained has a densityof (0,8976±0,0003 g/mL), viscosity of (4,53±0,0872 mm/s), acid value of (0,4238±0,0397 mg KOH/g, and iodnumber of (9,3354±0,0288 g iod/100 g sample). There properties were in a good agreement with the standard JermanDIN 51606.